Study of the side gate junctionless transistor in accumulation region - Dehzangi, Arash; Larki, Farhad; Md Ali, Sawal Hamid; Hutagalung, Sabar Derita; Islam, Md Shabiul; Hamidon, Mohd Nizar; Menon, Susthitha; Jalar @ Jalil, Azman; Hassan, Jumiah; Yeop Majlis, Burhanuddin (Emerald, 2016)
Mohd. Nizar Hamidon/ Jumiah Binti Hassan/ Arash Dehzangi/ Farhad Larki, Sawal Hamid Md Ali, Sabar Derita Hutagalung, Burhanuddin Yeop Majlis